PERENCANAAN SALURAN IRIGASI SEKUNDER D.I BATANG TAMBANGAN JORONG LUNDAR NAGARI PANTI TIMUR KECAMATAN PANTI - KAB. PASAMAN - M.Azi Saputra; Masril Masril; Ana Susanti Yusman (Ensiklopedia Research and Community Service Review, 2022)
The existence of the flow of water from one place to another has a stream whose irrigation buildings are still walled so that many plots of people's rice fields are not fed by the flow of water. Like the Jorong Lundar area which has a rice field area of ± 150 ha. However, irrigation channels are still not smooth and there are still many rice fields that are not fed by water. Various efforts have been made to increase food production yields, but there are still many people who cannot grow rice. The researcher reviewed how the water shortage was in the Jorong Lundar rice field area and calculated the water discharge requirement for the flow of water to the rice fields. Data collection in this study is divided into two, namely primary and secondary data collection and uses rainfall data for the last 10 years. processing the data using the harsper method and the gumbel method. Based on the calculation of the design dimensions of the channel with a cross-sectional area of 1.7 m² and the channel discharge when flood water is 2.87 m³/sec, the results of secondary irrigation canal planning are obtained where Q 5.65 m3/s is able to accommodate the highest water discharge with Qmax 2, 87 m3/s. The results of calculations using the Gumbel method for R 5 TH are 130 mm, the results of calculations using Harspers are 2.87 m3/sec. The results of data analysis and calculations are expected to be used as input and reference by the relevant agencies. It is necessary to have an active role from the community so that they can maintain the smooth process of irrigating water and maintain water structures so that the irrigation area can provide benefits to the agricultural community. Keywords: Harsper Method, Gumbel Method, Irrigation, Secondary Canal